A Mendelian randomization study of the effect of serum 25-hydroxyvitamin D levels on autoimmune thyroid disease - Yu, Yunfeng; Yang, Xinyu; Wu, Jingyi; Shangguan, Xueli; Bai, Siyang; Yu, Rong (Frontiers in Immunology, 2024)
Objective The influence of vitamin D on autoimmune thyroid disease (AITD) remains a subject of ongoing debate. This study employs Mendelian randomization (MR) to investigate the causal correlations of serum 25-hydroxyvitamin D (25[OH]D) levels with autoimmune thyroiditis (AIT), autoimmune hyperthyroidism (AIH), and Graves disease (GD). Methods Data on single nucleotide polymorphisms related to serum 25(OH)D levels, AIT, AIH, and GD were sourced from UK Biobank and FinnGen. Inverse variance weighted, MR-Egger, and weighted median were employed to test the exposure-outcome causal relationship. Assessments of horizontal pleiotropy, heterogeneity, and stability were performed using the MR-Egger intercept, Cochran’s Q test, and leave-one-out sensitivity analysis, respectively. Results The results of MR analysis showed increased serum 25(OH)D levels was associated with a reduced risk of AIT (OR 0.499, 95% CI 0.289 to 0.860, p = 0.012) but not causal associated with AIH (OR 0.935, 95% CI 0.695 to 1.256, p = 0.654) and GD (OR 0.813, 95% CI 0.635 to 1.040, p = 0.100). Intercept analysis showed no horizontal pleiotropy (p > 0.05), and Cochran’s Q test showed no heterogeneity (p > 0.05). Sensitivity analysis suggested that these results were robust. Conclusion An increased serum 25(OH)D level is associated with AIT risk reduction but unrelated to AIH and GD. This finding suggests that vitamin D supplementation can be valuable for preventing and treating AIT.